2015
DOI: 10.3171/2015.6.peds15184
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weekend and after-hours surgery on morbidity and mortality rates in pediatric neurosurgery patients

Abstract: P ediatric neurosurgeons frequently perform emergency surgical procedures outside "regular" operating room hours due to the time-sensitive nature of disease processes and because delays in care may contribute to adverse outcomes. However, operating room staffing and hospital resource availability are variable outside of the conventional Monday through Friday work week.There is a growing body of literature that suggests increased rates of morbidity and mortality for a number of pediatric and adult conditions wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
3
25
1
Order By: Relevance
“…There appears to be a weekend effect regarding certain procedural complications. In a retrospective cohort of 580 patients less than 18 years of age undergoing 710 urgent or emergency neurosurgical procedures in a Texas Children’s Hospital, there was a significant excess of surgical complications at weekends and weekdays after-hours 10. In a small study of 28 patients undergoing oesophageal atresia and trachea-oesophageal repair, there were significantly more oesophageal leaks in those admitted after-hours23 and this was associated with a longer postoperative length of ventilation (16.1 vs 9.3 days) 23.…”
Section: Introductionmentioning
confidence: 99%
“…There appears to be a weekend effect regarding certain procedural complications. In a retrospective cohort of 580 patients less than 18 years of age undergoing 710 urgent or emergency neurosurgical procedures in a Texas Children’s Hospital, there was a significant excess of surgical complications at weekends and weekdays after-hours 10. In a small study of 28 patients undergoing oesophageal atresia and trachea-oesophageal repair, there were significantly more oesophageal leaks in those admitted after-hours23 and this was associated with a longer postoperative length of ventilation (16.1 vs 9.3 days) 23.…”
Section: Introductionmentioning
confidence: 99%
“…There were studies that documented surgeries done afterhours carried higher morbidity and mortality. [3][4][5][6][7][8][9][10][11] Chacko et al 3 performed a retrospective study of 767 consecutive patients with intertrochanteric, subtrochanteric, or femoral neck fractures and found that the duration of surgery, blood loss, and postoperative mortalities were significantly less for surgery done during the day compared with night. Ricci et al 4 conducted a prospective study among 203 patients with femur and tibia fractures comparing surgeries done at daytime and after-hours.…”
Section: Discussionmentioning
confidence: 99%
“…Kelz et al 6 reported a retrospective study of 144,740 nonemergent general and vascular surgical procedures, comparing the operation start time of 7 a.m. to 4 p.m., 4 p.m. to 6 p.m., and 6 p.m. to 11 p.m. and found that morbidity was significant higher when the operation start time was later in the day. Desai et al 7 performed a retrospective study on 710 urgent or emergency pediatric neurosurgical procedures and found that 30-day morbidity and mortality were significantly higher when these procedures were done during the weekend or after-hours. Komen et al 8 found that anastomosis leakage was significantly higher among patient who underwent a primary colorectal anastomosis operation during after-hours compared with daytime.…”
Section: Discussionmentioning
confidence: 99%
“…The Hospital Authority (HA) (10)) were selected from CDARS. Records were also reviewed through the CMS for verification.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] Scant literature on the effect of time of the day of operation on hip surgery outcome shows controversial results.…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%